PENGARUH PROMOSI, BRAND IMAGE DAN LOKASI TERHADAP KEPUASAN KONSUMEN PADA PEMBELIAN ROTI DITOKO JANNAH BAKERY DI BESUKI KABUPATEN SITUBONDO - Maulany Ayu Safitri; Karnadi Karnadi; Riska Ayu Pramesthi (Jurnal Mahasiswa Entrepreneurship (JME), 2026)
This study aims to determine the effect of promotion, brand image and location on consumer satisfaction in purchasing bread at the Jannah Bakery shop in Besuki, Situbondo Regency. The data analysis methods used in this research are validity test, reliability test, classical assumption test, multiple linear regression analysis, t test, f test, dominant test, and coefficient of determination. Multiple linear regression results show that Y= 4.799E-17 + 0.537X1 + 0.314X2 + 0.161X3 + e indicates the value for the promotion variable is tcount 7.022 > ttable 1.985, meaning that the promotion variable has a partial effect on consumer satisfaction. The value for the brand image variable is tcount 5.498 > ttable 1.985, meaning that the brand image variable has a partial effect on consumer satisfaction. The value for the location variable is 2.232, so tcount > 2.232 ttable 1.985, meaning that the location variable has a partial effect on consumer satisfaction in purchasing bread at the Jannah bakery shop in Besuki, Situbondo Regency. The F test shows Fcount 143.518 > Ftable 2.70 so it can be concluded that the research hypothesis (H2) states that the variables of promotion, brand image, and location have a simultaneous effect on consumer satisfaction. Based on the dominant test the value of the promotion variable is greater than the other variables 7.022.